Pipeline integrity handbook risk management and evaluation - Singh, R.P. (Ramesh P.) (Gulf Professional Pub., 2014)
This book provides pipeline engineers with the tools to evaluate and inspect pipelines, safeguard the life cycle of their pipeline asset, and ensure that they are optimizing delivery and capability.